Pengembangan LKPD Berbantuan Aplikasi Bookcreator dan Aplikasi Flipbook pada Materi Teks Anekdot pada Siswa Kelas X SMA PAB 8 Saentis - Melani, Siti Eliza; Andriany, Liesna; Ali, Ali (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2025)
This study aims to describe the development process, feasibility, and effectiveness of E-LKPD (Electronic Student Worksheets) assisted by Bookcreator and Flipbook for teaching anecdotal texts to 10th-grade students at SMA PAB 8 Saentis. The research adopts a Research and Development (R&D) methodology following the Thiagarajan 4-D model (Define, Design, Develop, Disseminate). The validation results indicate that the E-LKPD received a 72% feasibility score from content experts (categorized as "fairly feasible") and an 84% feasibility score from design experts (categorized as "highly feasible"). Student responses were overwhelmingly positive, reaching 92%, indicating strong engagement and satisfaction with the learning media. Additionally, the implementation of the E-LKPD resulted in a significant improvement in students' learning outcomes, demonstrating its effectiveness in enhancing comprehension of anecdotal texts. These findings suggest that E-LKPD, supported by Bookcreator and Flipbook, is a valid, effective, and feasible instructional tool for digital-based learning environments.